Analisis Rasio Solvabilitas Untuk Menilai Kinerja Keuangan PT.Bank Syariah Indonesia KCP Kabupaten Kolaka - Yanti, Septi Rindi; Kartomo; Sabarudin (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This study aims to determine the Solvency Ratio Analysis to Assess Financial Performance of PT. Bank Syariah Indonesia KCP Kolaka Regency. This study uses a Qualitative research method with a descriptive approach. In collecting data, researchers use data collection techniques, namely interviews and documentation. The data analysis technique used is the solvency ratio formula. The results of the study show that the financial performance of PT Bank Syariah Indonesia Tbk Kolaka Branch from 2021 to 2023 based on the Debt to Asset Ratio is in a fairly healthy condition. Because, based on the standard ratio value, it is stated <40%, which is considered fairly healthy. The financial performance of PT Bank Syariah Indonesia Tbk from 2021 to 2023 based on the Debt to Equity Ratio is in a very unhealthy condition. Because, based on the standard ratio value, it is stated <200%, which is considered very unhealthy.